2014
DOI: 10.1111/j.1475-5890.2014.12028.x
|View full text |Cite
|
Sign up to set email alerts
|

Panel Data Evidence on the Effects of Fiscal Policy Shocks in the EU New Member States

Abstract: We identify fiscal policy shocks in the EU new member states using four different methods. We use panel data techniques to estimate the output response to these shocks. We find that investment and export growth increase after fiscal consolidation and decelerate after fiscal stimulus when the shocks are expenditure-based. In contrast, private consumption does not respond to fiscal policy shocks. Expenditure-based fiscal consolidations reduce wages, supporting the view that fiscal consolidation of such compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 68 publications
1
12
0
2
Order By: Relevance
“…3 Most economists believe that direct taxes have a stronger negative impact on growth than indirect taxes. This premise is examined in many empirical studies such as Gemell (2013), Borys (2014), Surugiu (2012) and others. Machová and Kotlán (2014a) show that indirect taxes only influence trade-off decisions between work and leisure.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Most economists believe that direct taxes have a stronger negative impact on growth than indirect taxes. This premise is examined in many empirical studies such as Gemell (2013), Borys (2014), Surugiu (2012) and others. Machová and Kotlán (2014a) show that indirect taxes only influence trade-off decisions between work and leisure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Alesina (1996), Alesina (2009) and Hagen (2002) have all examined the impacts of fiscal adjustments. A recent study by Borys (2014) demonstrated that a 1 percent GDP tax-based fiscal consolidation slows private investment growth by 0.77 percentage points. Expenditure-based consolidation of the same size however results in an improvement in private investment by 3.19 percentage points on average.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wahania globalnej awersji do ryzyka mierzone są na ogół różnicą pomiędzy oprocentowaniem obligacji rządowych Stanów Zjednoczonych i obarczonych średnim bądź wysokim ryzykiem obligacji korporacyjnych 12 . Alternatywnie wykorzystywaną zmienną jest wartość indeksu zmienności VIX 13 , przy czym jej zastosowanie nie zmienia najważniejszych wniosków o silnej statystycznej istotności tego zjawiska 14 . Jeszcze inne zmienne wykorzystują (z podobnym skutkiem) Cagggiano, Greco 15 .…”
Section: Przegląd Literaturyunclassified
“…Most economists believe that direct taxes have more negative impact on economic growth than the indirect taxes, e.g. Borys (2014). According to Banks (2010) and (Barbone and coll., 2015), a number of studies have confirmed the significant impact of tax policy on the business environment.…”
Section: Introductionmentioning
confidence: 99%